Career development impact on architecture undergrads’ employment: learning motivation mediation - Zi Ming Fan; Juo-Lan Yeh (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study, utilizing the expectancy-value theory, examines the relationship between career development, learning motivation, and employment capabilities among Chinese architecture undergraduates. Surveying 319 students from five Chinese universities, the research reveals that career development has a positive impact on both employment capabilities and learning motivation. Learning motivation, in turn, positively affects employment capabilities and acts as a mediator between career development and employment capabilities. These findings underscore the significance of proactive career planning, goal setting, and intrinsic learning motivation in enhancing students' employment capabilities. For practical applications, educational institutions can design comprehensive career development programs to assist students in defining career goals and igniting intrinsic motivation for learning, thereby fostering career success and employability among architecture students.